Critical thinking skills for dummies - Cohen, Martin (for dummies., 2024)
The ability to think clearly and critically is a lifelong benefit that you can apply in any situation that calls for reflection, analysis, and planning. Being able to think systematically and solve problems is also a great career asset. Critical Thinking Skills For Dummies helps you hone your thinking abilities and become a better communicator. You’ll find hands-on, active instruction and exercises that you can put to work today as you navigate social media and news websites, chat with AI, fact-check your own and others’ views, and more. Become a thinking machine with this Dummies guide